MELATIH KEMAMPUAN BERPIKIR KRITIS DENGAN METODE TEACHING GAMES fOR UNDERSTANDING (TGfU) MATA PELAJARAN PENJASORKES SISWA SEKOLAH MENENGAH PERTAMA (SMP) DI KOTA PONTIANAK - Iskandar Iskandar; Heri Rustanto (IKIP PGRI Pontianak, 2023)
The aim of this research is to train critical thinking skills using the teaching games for understanding (TGfU) method for physical education subjects for students in junior high school physical education subjects in Pontianak City. The research and product development model that is the basis for this research is the Dick & Carey instructional design model. The population in this research are students in junior high school physical education subjects in Pontianak City. The researcher's sampling technique that will be used is total sampling. The data collection technique used is the observation technique. The technique used to analyze the data in this research is descriptive qualitative. Based on the results of the recapitulation of the first trial data, the key score in the Game Performance Assessment Instrument (GPAI) Test/Football Game Performance guidelines obtained at this initial stage was an average of 86 actions for each indicator, which means that effective performances often appear. This category means that students' critical thinking abilities are quite good as seen from students' decisions in playing basketball. In order to optimize students' critical thinking abilities, interactions between educators and students are needed to reflect the behavior (effects) of teaching and learning in certain conditions. In the trial phase 2, the average action of each indicator changed, based on the key score table, which means that effective performance always appears. This category means that students' critical thinking abilities are optimal as seen from the students' support in playing basketball. Based on products developed through expert tests and field tests, the Guide to training critical thinking in Physical Education subjects for Junior High School (SMP) Students in Pontianak City is suitable for use in Physical Education learning.